Model Manajemen Praktikum Pendidikan Berbasis E-praktek: Kolaborasi Guru dan Siswa untuk Pembelajaran Aktif dan Berbasis Produk - Akhmad Ghasi Pathollah (Universitas Nurul Jadid, 2026)
This study develops an E-Practice–based practicum management model to foster active, product-oriented learning through teacher–student collaboration in junior high schools (SMP) in Bondowoso, Indonesia. The work responds to persistent challenges in conventional classroom practices, limited collaborative scaffolding, and the lack of systematic progress monitoring and authentic assessment in project-based settings. A Research and Development (R&D) approach was employed, including literature review and needs analysis, system design using UML (use case, sequence, class, and activity diagrams), application development, expert validation, and limited field testing. The E-Practice platform is implemented as a responsive web system with a three-tier architecture and role-based interfaces (teacher, student, administrator). Core functionalities include project authoring, task management, evidence/document uploads, discussion and feedback spaces, real-time progress tracking, and an integrated rubric-based assessment separating academic achievement, collaboration, and Pancasila Student Profile (P5) dimensions. The platform also provides project dashboards, full-project data recapitulation, and data visualization to support reflection and data-driven decision making. The development results indicate that E-Practice can systematically integrate PBL project management with P5 character reinforcement in a structured, transparent, and well-documented workflow, strengthening the feasibility of sustainable project-based learning implementation in schools